Welcome to Westonci.ca, where curiosity meets expertise. Ask any question and receive fast, accurate answers from our knowledgeable community. Join our platform to get reliable answers to your questions from a knowledgeable community of experts. Experience the convenience of finding accurate answers to your questions from knowledgeable experts on our platform.
Sagot :
To find [tex]\((f \cdot g)(x)\)[/tex], where [tex]\(f(x) = \sqrt{2x}\)[/tex] and [tex]\(g(x) = \sqrt{18x}\)[/tex], we need to multiply these two functions together.
Starting from the given functions:
[tex]\[ f(x) = \sqrt{2x} \][/tex]
[tex]\[ g(x) = \sqrt{18x} \][/tex]
The product of [tex]\(f(x)\)[/tex] and [tex]\(g(x)\)[/tex] is:
[tex]\[ (f \cdot g)(x) = f(x) \cdot g(x) \][/tex]
Substituting the expressions for [tex]\(f(x)\)[/tex] and [tex]\(g(x)\)[/tex]:
[tex]\[ (f \cdot g)(x) = \sqrt{2x} \cdot \sqrt{18x} \][/tex]
To multiply these two square roots together, we can combine the contents under a single square root:
[tex]\[ (f \cdot g)(x) = \sqrt{(2x) \cdot (18x)} \][/tex]
Multiplying the terms inside the square root:
[tex]\[ (f \cdot g)(x) = \sqrt{36x^2} \][/tex]
Next, simplify the square root:
[tex]\[ \sqrt{36x^2} = \sqrt{36} \cdot \sqrt{x^2} \][/tex]
Since [tex]\(\sqrt{36} = 6\)[/tex] and [tex]\(\sqrt{x^2} = x\)[/tex] for [tex]\(x \geq 0\)[/tex]:
[tex]\[ \sqrt{36x^2} = 6x \][/tex]
Thus, we have:
[tex]\[ (f \cdot g)(x) = 6x \][/tex]
Therefore, the correct answer is:
[tex]\[ \boxed{6x} \][/tex]
Starting from the given functions:
[tex]\[ f(x) = \sqrt{2x} \][/tex]
[tex]\[ g(x) = \sqrt{18x} \][/tex]
The product of [tex]\(f(x)\)[/tex] and [tex]\(g(x)\)[/tex] is:
[tex]\[ (f \cdot g)(x) = f(x) \cdot g(x) \][/tex]
Substituting the expressions for [tex]\(f(x)\)[/tex] and [tex]\(g(x)\)[/tex]:
[tex]\[ (f \cdot g)(x) = \sqrt{2x} \cdot \sqrt{18x} \][/tex]
To multiply these two square roots together, we can combine the contents under a single square root:
[tex]\[ (f \cdot g)(x) = \sqrt{(2x) \cdot (18x)} \][/tex]
Multiplying the terms inside the square root:
[tex]\[ (f \cdot g)(x) = \sqrt{36x^2} \][/tex]
Next, simplify the square root:
[tex]\[ \sqrt{36x^2} = \sqrt{36} \cdot \sqrt{x^2} \][/tex]
Since [tex]\(\sqrt{36} = 6\)[/tex] and [tex]\(\sqrt{x^2} = x\)[/tex] for [tex]\(x \geq 0\)[/tex]:
[tex]\[ \sqrt{36x^2} = 6x \][/tex]
Thus, we have:
[tex]\[ (f \cdot g)(x) = 6x \][/tex]
Therefore, the correct answer is:
[tex]\[ \boxed{6x} \][/tex]
Thanks for using our service. We're always here to provide accurate and up-to-date answers to all your queries. Thank you for your visit. We're dedicated to helping you find the information you need, whenever you need it. Get the answers you need at Westonci.ca. Stay informed by returning for our latest expert advice.